Immunogenicity of an adjuvanted SARS-CoV-2 trimeric S-protein subunit vaccine (SCB-2019) in SARS-CoV-2-naïve and exposed individuals in a phase 2/3, double-blind, randomized study. Issue 11 (10th March 2023) - Buntinx, Erik; Brochado, Leonardo; Borja-Tabora, Charissa; Yu, Charles Y.; Alberto, Edison R; Montellano, May Emmeline B.; Carlos, Josefina C.; Toloza, Leonardo Bautista; Hites, Maya; Siber, George; Clemens, Ralf; Ambrosino, Donna; et al.
Highlights: SCB-2019 is a protein subunit vaccine candidate against COVID-19. SCB-2019 contains the SARS-CoV-2 spike protein adjuvanted with CpG-1018/alum. A single dose of SCB-2019 was immunogenic in SARS-CoV-2-exposed individuals. Two doses are required to induce immune response in SARS-CoV-2-naïve individuals. SCB-2019 induced cross-reactive neutralizing antibodies to SARS-CoV-2 variants. Abstract: Background: We evaluated immunogenicity of SCB-2019, a subunit vaccine candidate containing a pre-fusion trimeric form of the SARS-CoV-2 spike (S)-protein adjuvanted with CpG-1018/alum. Methods: The phase 2/3, double-blind, randomized SPECTRA trial was conducted in five countries in participants aged ≥ 18 years, either SARS-CoV-2-naïve or previously exposed. Participants were randomly assigned to receive two doses of SCB-2019 or placebo administered intramuscularly 21 days apart. In the phase 2 part of the study, on days 1, 22, and 36, neutralizing antibodies were measured by pseudovirus and wild-type virus neutralization assays to SARS-CoV-2 prototype and variants, and ACE2-receptor-binding antibodies and SCB-2019–binding antibodies were measured by ELISA. Cell-mediated immunity was measured by intracellular cytokine staining via flow cytometry. Results: 1601 individuals were enrolled between 24 March and 13 September 2021 and received at least one vaccine dose. Immunogenicity analysis was conducted in a phase 2 subset of 691 participants, including 428 SARS-CoV-2-naïve (381 vaccine and 47 placebo recipients) and 263 SARS-CoV-2-exposed (235 vaccine and 28 placebo recipients). In SARS-CoV-2-naïve participants, GMTs of neutralizing antibodies against prototype virus increased 2 weeks post-second dose (day 36) compared to baseline (224 vs 12.7 IU/mL). Seroconversion rate was 82.5 %. In SARS-CoV-2-exposed participants, one SCB-2019 dose increased GMT of neutralizing antibodies by 48.3-fold (1276.1 IU/mL on day 22) compared to baseline. Seroconversion rate was 92.4 %. Increase was marginal post-second dose. SCB-2019 also showed cross-neutralization capability against nine variants, including Omicron, in SARS-CoV-2-exposed participants at day 36. SCB-2019 stimulated Th1-biased cell-mediated immunity to the S-protein in both naïve and exposed participants. The vaccine was well tolerated, no safety concerns were raised from the study. Conclusions: A single dose of SCB-2019 was immunogenic in SARS-CoV-2-exposed individuals, whereas two doses were required to induce immune response in SARS-CoV-2-naïve individuals. SCB-2019 elicited a cross-neutralizing response against emergent SARS-CoV-2 variants at antibody levels associated with clinical protection, underlining its potential as a booster. Clinicaltrials.gov: NCT04672395; EudraCT: 2020-004272-17.